2010
DOI: 10.4012/dmj.2009-064
|View full text |Cite
|
Sign up to set email alerts
|

Can intra-coronally bleached teeth be bonded safely after antioxidant treatment?

Abstract: The aim of this study was to compare the effects of antioxidant treatment and delayed bonding, following intra-coronal bleaching, on the shear bond strength (SBS) and bond failure site of brackets bonded to enamel. Eighty mandibular incisors were divided into four equal groups. After root canal filling, specimens in Group 1 were used as control and not bleached. For experimental groups 2 to 4, bleaching agent was placed into the rest of the cavity for a four-day period and this bleaching treatment was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…They suggested that lower SBS could be due to changes in enamel structure resulting from increased porosity or reduction of the microhardness of dentin and enamel by the loss of calcium. In agreement with Uysal et al, 12,13 lower SBS in all bleaching groups was observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…They suggested that lower SBS could be due to changes in enamel structure resulting from increased porosity or reduction of the microhardness of dentin and enamel by the loss of calcium. In agreement with Uysal et al, 12,13 lower SBS in all bleaching groups was observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…12,13 In both of these studies, Uysal et al 12,13 reported that intracoronal bleaching with 16% carbamide peroxide adversely affected the SBS of brackets bonded immediately after bleaching or 30 days after bleaching. They suggested that lower SBS could be due to changes in enamel structure resulting from increased porosity or reduction of the microhardness of dentin and enamel by the loss of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common techniques to restore bond strength after bleaching procedures is to delay the bonding procedure after bleaching 7. Another technique to avoid such a delay and enable immediate bonding after bleaching procedures is to apply antioxidative agents.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies, which tested the effectiveness of AS in reversing compromised bond strengths, used carbamide peroxide at low concentrations [5,[7][8][9][10][11][12][13][14][15][16]20,21,25,[28][29][30]33]. It is possible that SA was more effective in teeth bleached with carbamide peroxide due the hydrogen peroxide releases a high oxygen concentration [37].…”
Section: Sodium Ascorbate Versus Bleaching Agent Typementioning
confidence: 99%